LIFE LIVED IN LOVE: KONSEP JÜRGEN MOLTMANN MENGENAI ESKATOLOGI PRIBADI | LIFE LIVED IN LOVE: JÜRGEN MOLTMANN’S CONCEPT ON PERSONAL ESCHATOLOGY - Jessica Novia Layantara (Jurnal Ledalero, 2018)
Abstract This article will focus on describing Moltmann’s view of personal eschatology, which includes his view on death, the intermediate state, the resurrection of the dead, and eternal life. The main thesis of this article is that Moltmann’s view of personal eschatology is more relevant and applicable to the Christian life here and now. At the end of this article, the author will give two applications of Moltmann’s doctrine of personal eschatology. First, Moltmann’s view of personal eschatology motivates Christians, that they must live their lives in love, hope, and faith, for they already have been resurrected and given eternal life, here and now. Secondly, Moltmann’s focus on the new earth and new heaven in this world, more than life after death and the traditional concepts of heaven and hell, should make Christians care about this world and the life in it. Keywords: Jürgen Moltmann, Personal Eschatology, Death, Intermediate State, Resurrection of the Dead, Eternal Life. Abstrak Artikel ini terfokus pada deskripsi pandangan Moltmann tentang eskatologi pribadi, yaitu mengenai kematian, keadaan peralihan, kebangkitan orang mati, dan kehidupan kekal. Tesis utama artikel ini ialah pandangan Moltmann tentang eskatologi pribadi yang lebih relevan dan berlaku untuk kehidupan Kristen di sini dan saat ini. Pada akhir artikel ini, penulis memberikan dua aplikasi dari doktrin Moltmann tentang eskatologi pribadi, yaitu: Pertama, pandangan Moltmann tentang eskatologi pribadi memotivasi orang Kristen supaya menjalani hidup mereka dalam cinta, harapan, dan iman, karena mereka sudah dibangkitkan dan diberikan jaminan kehidupan kekal. Kedua, pandangan Moltmann mengenai bumi dan surga baru di dunia ini yang lebih dari kehidupan setelah kematian dan konsep-konsep tradisional tentang surga dan neraka, membuat orang Kristen peduli terhadap dunia dan kehidupan di dalamnya. Kata kunci: Jürgen Moltmann, Eskatologi Pribadi, Kematian, Kebangkitan Orang Mati, Kehidupan Kekal